Application of the dilatometer test for estimating undrained shear strength of Busan New Port clay. (15th March 2016) - Choo, Hyunwook; Lee, Woojin; Hong, Sung-Jin; Lee, Changho
Abstract: The dilatometer test (DMT) is an economical and fast tool that evaluates the stratigraphy and properties of soil. In this study, a series of DMTs, field vane tests (FVTs), and K 0 consolidated-undrained triaxial compression (CK0 UC) tests were performed to develop an empirical correlation for the undrained shear strength ( su ) of clayey soils from the Busan New Port site. The stress-normalized mobilized su ( μ s u / σ v ′ ) for both laboratory tests and FVTs is determined to be around 0.22, which is consistent with previous studies. The exponent m for overconsolidation ratio (OCR), which is in the relation of s u / σ v ′ = S · OCR m, is determined to be 0.83 by using the SHANSEP technique. Two different methods of estimating su are reviewed to make use of either the horizontal stress index ( KD ) or the bearing factor ( Nc ). Because the DMT results indicate that the Nc is linearly proportional to the material index ( ID ), representing the characteristics of soil, the empirical su estimating formula with ID is newly suggested in this study. According to the values for the mean absolute percentage error (MAPE), the empirical correlation with ID shows a slightly better accuracy than that using KD . However, a comparison between the values for the su that are measured and estimated by using two different methods shows good agreement in general. Highlights: Two different methods are reviewed and suggested to predict the su according to the results of the DMT. The overall trends for all of the estimated μsu using both KD and ID are in good agreement with the μsu values measured, regardless of the test methods.